1996
DOI: 10.1101/gad.10.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Targeted in vivo expression of the cyclin-dependent kinase inhibitor p21 halts hepatocyte cell-cycle progression, postnatal liver development and regeneration.

Abstract: The CDK inhibitor p21 (WAF-1/CIP-1/SDI-1) has been implicated in DNA damage-induced p53-mediated G~ arrest, as well as in physiological processes, such as cell differentiation and senescence, that do not involve p53 function. To determine the impact of p21 on normal development and cell-cycle regulation in vivo, we have generated transgenic mice that abundantly express p21 specifically in hepatocytes. During postnatal liver development, when transgenic p21 protein becomes detectable, hepatocyte proliferation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
181
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(207 citation statements)
references
References 68 publications
23
181
2
1
Order By: Relevance
“…Although further studies are therefore required to further elucidate this relationship, the concept of cellular senescence warrants further consideration as replicative arrest affecting a large proportion of hepatocytes might significantly compromise the regenerative capacity of the liver in these cases. Furthermore, previous studies have suggested that p21 plays a key role in regulation of hepatocyte G1 phase progression and that transgenic mice with forced hepatic expression of p21 have markedly impaired regeneration after partial hepatectomy 29, 30…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies are therefore required to further elucidate this relationship, the concept of cellular senescence warrants further consideration as replicative arrest affecting a large proportion of hepatocytes might significantly compromise the regenerative capacity of the liver in these cases. Furthermore, previous studies have suggested that p21 plays a key role in regulation of hepatocyte G1 phase progression and that transgenic mice with forced hepatic expression of p21 have markedly impaired regeneration after partial hepatectomy 29, 30…”
Section: Discussionmentioning
confidence: 99%
“…Since expression of either p27 Kip1 or p21 Waf1 can result in cell cycle arrest (Toyoshima and Hunter, 1994;Wu et al, 1996), their di erent regulation by activated K-ras cannot be perceived as a simple cell cycle e ect. The same logic would be applicable to p53 and Gadd 45.…”
Section: Discussionmentioning
confidence: 99%
“…Three independent lines of mice, TTR1-KLF6, TTR4-KLF6 and TTR9-KLF6, were generated with modest (Btwo-to threefold) but reproducible expression of KLF6. Expression of the transgene is confined specifically to hepatocytes with variable expression in the choroid plexus of the brain at high transgene copy number (Wu et al, 1996) (data not shown). TG mice were analysed at 6 weeks of age as this is the period of rapid murine liver growth and differentiation (Walthall et al, 2005), and studies of mice with hepatocyte specific overexpression of p21 (Wu et al, 1996) demonstrated a significant phenotype during this time period.…”
mentioning
confidence: 94%
“…Expression of the transgene is confined specifically to hepatocytes with variable expression in the choroid plexus of the brain at high transgene copy number (Wu et al, 1996) (data not shown). TG mice were analysed at 6 weeks of age as this is the period of rapid murine liver growth and differentiation (Walthall et al, 2005), and studies of mice with hepatocyte specific overexpression of p21 (Wu et al, 1996) demonstrated a significant phenotype during this time period. Compared with wild-type (WT) littermates, KLF6 TG mice had diminished body weight and liver mass, with reduced serum albumin levels; serum-alanine aminotransferase (ALT) and -aspartate aminotransferase (AST) levels were normal, however, indicating a lack of hepatocyte injury, as documented also by lack of inflammatory infiltrates within the liver (Table 1).…”
mentioning
confidence: 94%
See 1 more Smart Citation